The Efforts to Improve Students' Speech Skills by Using The TPR (Total Physical Response) Learning Method in Grade IX Students of Al-Ihsan Junior High School - Alfika Septia Rizpawa; Izzuddin Musthafa; Isop Syafei; Ade Arip Ardiansyah (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to improve students' maharatul kalam (speaking skills) through the implementation of the Total Physical Response (TPR) teaching method in class IX A at SMP al-Ihsan. The TPR method is a language teaching approach that combines physical movement with verbal instructions, designed to create a more enjoyable and effective learning environment. This research employs a classroom action research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of this study are 15 students from class IX A at SMP al-Ihsan. Data were collected through observation, pre-tests, and post-tests related to maharatul kalam. Data analysis was performed using quantitative descriptive methods with product moment correlation testing and paired t-tests. The results of the study indicate that the implementation of the TPR method significantly improves students' maharatul kalam. Students also reported that learning with the TPR method is more engaging and helps them more easily remember and use new vocabulary in everyday conversations. The TPR method has proven effective in enhancing the speaking skills of students in class IX A at SMP al-Ihsan. This method not only increases student participation and learning motivation but also improves their learning outcomes in speaking skills. Therefore, it is recommended that language teachers consider implementing the TPR method in their teaching processes to enhance students' speaking competencies. This study also suggests further research with larger samples and varied learning contexts to test the effectiveness of the TPR method more broadly.